The law of sports and entertainment in Uganda - Lubogo, Isaac Christopher (Jescho Publishing House, 2022)
Sports can be defined as institutionalized competitive activity which involves two or more opponents and stresses physical exertion by serious competitors who represent or are part of formally organized associations. According to the Oxford Dictionary, sport is an amusement, diversion, fun, pastime and game. Sports have been differentiated from games on the basis of the high physical skill factor they involve, and a sociologist has defined sport as institutionalized competitive activity which involves two or more opponents and stresses physical exertion by serious competitors who represent or are part of formally organized associations. Others define, sport, as a combination of physical and mental activity, governed by a set of rules or customs with social, educational and cultural dimensions. According to Bellis Mary, the documented history of sports goes back to at least 3000 years. In the beginning, sports often involved preparation for war or training as hunters which explain why so many early games involved throwing of spears, stones and rocks and sparring one on one with opponents. The physical activity that developed into sports had early links with ritual, warfare and entertainment. As far back as the beginning of sport, it was related to military training. For example, competition was used as a means to determine whether individuals were fit and useful for services. With the first Olympic Games in 776 BC that included events such as foot and chariot races, wrestling, jumping, discus and javelin throwing the ancient Greeks introduced formal sports to the world.
Keywords: Sports law - Uganda; Entertainment law - Uganda